2005
DOI: 10.17660/actahortic.2005.690.1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Preferences Linked to Rose Taxonomy and Cytology

Abstract: The genus Rosa is usually subdivided into four subgenera, the largest of these is subgenus Rosa with 10 sections. Most of the genetically analysed rose species appear to be sexual and diploid (2n = 14) or tetraploid (2n = 28) although there are a few triploid (2n = 21), hexaploid (2n = 42) and octaploid species (2n = 56). The diploid species are usually self-incompatible whereas the polyploids are self-fertile. Pollen stainability is usually high in all species with even ploidy levels, i.e. 2x, 4x or 6x. Rose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…However, this seems unlikely because no trivalents were seen in the pentaploid R. canina, the frequency of chromosome pairing in the gynogenetic haploid was low and the molecular evidence (Werlemark et al, 1999;Wissemann, 1999;Nybom et al, 2004) indicates that only two of the five genomes of R. canina are closely similar. However, the formation of bivalents and trivalents in the gynogenetic haploid, albeit in low frequency, also demonstrates a limited potential for chromosome pairing between genomes of R. canina that was not expressed in the pentaploid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this seems unlikely because no trivalents were seen in the pentaploid R. canina, the frequency of chromosome pairing in the gynogenetic haploid was low and the molecular evidence (Werlemark et al, 1999;Wissemann, 1999;Nybom et al, 2004) indicates that only two of the five genomes of R. canina are closely similar. However, the formation of bivalents and trivalents in the gynogenetic haploid, albeit in low frequency, also demonstrates a limited potential for chromosome pairing between genomes of R. canina that was not expressed in the pentaploid.…”
Section: Discussionmentioning
confidence: 99%
“…If the matroclinal system of the Caninae evolved only once (Blackhurst, 1948;Werlemark, 2003;Nybom et al, 2004) and the genes that suppress homeologous pairing are located on the pairing chromosomes (Werlemark, 2003), bivalent-forming chromosomes throughout the Caninae are likely to be of common origin. This possibility is supported by the evidence of Nybom et al (2004) that the alleles shared by three pentaploid and one tetraploid species reside on the bivalent-forming chromosomes, whereas species-specific alleles reside on the univalent-forming chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ploidy levels were determined by flow cytometry in earlier studies (Nybom et al, 2004(Nybom et al, , 2006. All of these accessions were found to be pentaploid (2n ¼ 5x ¼ 35) except for R. mollis, which was tetraploid (2n ¼ 4x ¼ 28).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent molecular investigations have shed some light on the origin and structure of the individual subgenomes. Specifically, microsatellite DNA markers (Nybom et al, 2004(Nybom et al, , 2006, RAPD (Werlemark and Nybom, 2001) and nuclear ribosomal RNA genes (rDNA) (Kovarik et al, 2008a) have shown that the bivalent-forming genomes seem to be rather similar across different dogrose species, even those occurring in different subsections. In contrast, distinctly different univalent genomes occur within single genotypes, but also show levels of differentiation that are associated with taxonomic distances between genotypes.…”
Section: Introductionmentioning
confidence: 99%